(untitled) (Existential Analysis: Journal of the Society for Existential Analysis, 2006)
To say one’s practice is influenced by attachment research is a respectable claim. Yet the understanding of attachment is often muddied by natural psychological science’s focus on material being. Thus, conscious psychological senses and processes are discussed in terms of causative neurological development. Gaining an accurate understanding of attachment has an important role in addressing complex psychological phenomena, particularly when there is no consensus on how to proceed. How are attachment and intersubjectivity accurately identifiable? Intersubjectivity is capable of explaining attachment yet both terms need better definition and interrelation. This paper does not solve the problem of how to understand attachment and intersubjectivity. Rather, it attempts to demonstrate a series of problems in understanding attachment, everyday life and therapy as intersubjective. A scepticism is held concerning interpreting unconscious objects without relation to conscious ones. Consciousness is not an epiphenomenon. It is what needs explaining. Key words Attachment, intersubjectivity, co-empathy, interpretative stance.